Vieillir en « périphérie » québécoise: observer le vieillissement démographique du Québec à partir de la Gaspésie et des Îles. Issue 3 (2nd July 2020) - Lupien, Pierre-Luc
ABSTRACT: The future of the province of Quebec as always been linked with its demographic evolution. Today, 18% of Quebec society is more than 65 years old (Institut de la statistique du Québec 2017) and is third after Japan and South Korea (Azeredo et Payeur 2015) in terms of aging. Furthermore, peripheral regions tend to show this phenomenon even more. The highest rate can be observed in the administrative region of Gaspésie-Îles-de-la-Madeleine where one out of four people are more than 65 years old. Although very few studies are available on the consequences of this demographic reality, Lord, Negron-Poblete and Després (2017) discuss the diversity of socio-geographic context. Their comparative analysis is used to study the specifics of remote rural aging (Mallon 2014). The subtle signs of rural aging can be perceived by the knowing observer. Abandoned houses become slowly more visible in small remote towns while retirement homes are built in regional city centers. While slow to appear, these signs are evidence of a concentration process of the elderly population in regional service centers, which is confirmed by recent studies (Lupien 2016; Lupien 2018). This article explores how the population moves in an aging demographic territory. Gaspésie-Îles-de-la-Madeleine is at the peak of the aging curve of the province, and it helps us understand how Quebec can imagine its future through the experience of its peripheral regions.